2012
DOI: 10.3109/17435390.2012.697589
|View full text |Cite
|
Sign up to set email alerts
|

Gas-borne particles with tunable and highly controlled characteristics for nanotoxicology studies

Abstract: For nanotoxicology investigations of air-borne particles to provide relevant results it is ever so important that the particle exposure of, for example cells, closely resembles the “real” exposure situation, that the dosimetry is well defined, and that the characteristics of the deposited nanoparticles are known in detail. By synthesizing the particles in the gas-phase and directly depositing them on lung cells the particle deposition conditions in the lung is closely mimicked. In this work we present a setup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…For non-soluble particles, the particle surface area is attracting increasing interest as several studies have shown a close correlation with the toxicological response -a result that may be explained by the interactions at the interface between the particles and the exposed tissue or proteins body fluids (e.g., Stoeger et al, 2006). This particle property is however not always easy to attain for irregular particles (like soot agglomerates) (Messing et al, 2012), or particles containing soluble material with an insoluble core. Number concentration is sometimes more readily measured and has been indicated to be directly associated with health outcomes (Wittmaack, 2007).…”
Section: Respiratory Tract Depositionmentioning
confidence: 99%
“…For non-soluble particles, the particle surface area is attracting increasing interest as several studies have shown a close correlation with the toxicological response -a result that may be explained by the interactions at the interface between the particles and the exposed tissue or proteins body fluids (e.g., Stoeger et al, 2006). This particle property is however not always easy to attain for irregular particles (like soot agglomerates) (Messing et al, 2012), or particles containing soluble material with an insoluble core. Number concentration is sometimes more readily measured and has been indicated to be directly associated with health outcomes (Wittmaack, 2007).…”
Section: Respiratory Tract Depositionmentioning
confidence: 99%
“…The geometric mean diameter (GMD) is typically 20-40 nm (Messing et al 2012) while the aggregates produced with the HT are larger, 50-100 nm (mobility diameter) depending on the temperature used. The primary particle size of the aggregates, formed by both generators, is 5-15 nm.…”
Section: Sem Characterization Of Particle Morphology and Chemical Commentioning
confidence: 99%
“…The sampling was performed close to the emission zone during a session that included maintenance of both the HT and the SDG. (Messing et al 2012). …”
Section: Sem Characterization Of Particle Morphology and Chemical Commentioning
confidence: 99%
See 2 more Smart Citations